2017
DOI: 10.1038/srep40509
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid synthase 2 contributes to diapause preparation in a beetle by regulating lipid accumulation and stress tolerance genes expression

Abstract: Diapause, also known as dormancy, is a state of arrested development that allows insects to survive unfavorable environmental conditions. Diapause-destined insects store large amounts of fat when preparing for diapause. However, the extent to which these accumulated fat reserves influence diapause remains unclear. To address this question, we investigated the function of fatty acid synthase (FAS), which plays a central role in lipid synthesis, in stress tolerance, the duration of diapause preparation, and whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…The present study also revealed that fatty acid synthase (FAS) expression was also regulated by TcCBP. The FAS is another important player during diapause preparation in insects and lipid synthesis [ 83 ]. The transcription of FAS is suppressed by JH and the JH receptor Met.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also revealed that fatty acid synthase (FAS) expression was also regulated by TcCBP. The FAS is another important player during diapause preparation in insects and lipid synthesis [ 83 ]. The transcription of FAS is suppressed by JH and the JH receptor Met.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the function of insect FASN genes has been thoroughly studied only in some Drosophila species (Parvy et al, 2012;Chung et al, 2014;Wicker-Thomas et al, 2015). More recently, Tan et al (2017) showed that FASN silencing suppresses lipid accumulation, affecting stress tolerance and water content in female Colaphellus bowringi beetles undergoing diapause. In Drosophila serrata, RNAi-mediated knockdown of FASN3 using an oenocyte-specific driver was lethal, whilst knockdown of FASN2 led to a significant reduction in cuticle methyl-branched HCs, associated with a decrease in desiccation resistance (Chung et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…According to the KEGG pathway analysis, fifteen, six, and eleven pathways were observed as significantly enriched for DEGs of EggI vs. second instar, second vs. third instar, and third instar vs. adult females, respectively. The pathway enriched for different developmental stages were glycerolipid metabolism 69 , FoxO-signaling pathway 20 , 70 – 73 , Hippo signaling pathway 74 76 , fatty acid biosynthesis 77 – 79 , biosynthesis of amino acids 41 , 80 – 85 and steroid biosynthesis 86 88 suggesting that genes in these pathways seem to be involved in early developmental process. Likewise, we have identified all the genes coding for enzymes involved in juvenile and ecdysteroid hormone biosynthetic pathways and found many of them as potential RNAi targets for silencing (Fig.…”
Section: Discussionmentioning
confidence: 99%